The possibility of knowing - Sim, Vanessa Si Min (2015)
The action of a person reflects greatly on the level of thinking of that person individually. Divided into four levels, human think with feelings, beliefs, facts and ideas. As easy as it may sounds like, not many are able to practice the highest level of thinking – ideas. The ‘Ideation’ level reflects the humans’ ability in (1): constructing new realities, thus being able to build (2): a physical and mental environment – experience. [1] What intrigues me to embark onto this project is the possibility of pushing the existing boundary, “known” experience in the majority of the human race. Through (1) the construction of new realities – ‘light and sound’ is represented in this aspect, while (2) the tool to perceive this constructed reality of experience is executed through the use of synesthesia (the union of senses). Hence, through Ideation, the knowledge of knowing – experience, can be further enhanced.